(untitled) (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2013)
There is an abundance of anti-bullying programmes and bully prevention initiatives; yet bullying remains a serious problem. Educators are the key role-players in the development and implementation of a successful anti-bullying programme. An understanding of educators’ views on bullying is therefore a prerequisite in the prevention of bullying. The aim of this article is thus to report on findings from an empirical study that explored educators’ proposals on how to curb bullying. Educators, who were furthering their studies at the University of the Free State, were invited to take part in a study on different types of bullying. This article focuses on the prevention strategies of 91 participants who wrote about learner-onlearner bullying. A content analysis of the responses of the participants revealed that in accordance with Benbenishty and Astor’s social-ecological model, risk focused prevention should involve the school, the family and the community as interrelated ecological systems. Based on the findings, it is suggested that schools should try to involve as many individuals and groups as possible to develop and implement anti-bullying programmes. These programmes should recognise the role of the interrelated ecological systems in the prevention of bullying and cater for the distinctive needs of individual schools.